2021
DOI: 10.3390/w13212994
|View full text |Cite
|
Sign up to set email alerts
|

Water-Saving Efficiency and Inequality of Virtual Water Trade in China

Abstract: Virtual water trade is widely considered as a potential method to solve local water shortage and unequal distribution. However, limited research investigated water-saving efficiency and water inequality of inter-provincial virtual water trade. In this study, we sought to explore this issue within China based on the 2015 input-output data. A multi-regional input-output model and a modified input-output model were used to estimate the virtual water trade and its impact on water-saving and water inequality. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Rahman et al [79] concluded that water savings from a RWHs depend on climatic and demographic factors, often presenting considerable spatial variability. According to Xu et al [80], local water policies and strategies should be adapted to local water resources, efficiently resolving the conflict between water inequality and water conservation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rahman et al [79] concluded that water savings from a RWHs depend on climatic and demographic factors, often presenting considerable spatial variability. According to Xu et al [80], local water policies and strategies should be adapted to local water resources, efficiently resolving the conflict between water inequality and water conservation.…”
Section: Resultsmentioning
confidence: 99%
“…Rahman et al[79] concluded that water savings from a RWHs depend on climatic and demographic factors, often presenting considerable spatial variability. According to Xu et al[80], local water policies and strategies should be adapted to local water resources, efficiently resolving the conflict between water inequality and water conservation.The low-scale infrastructure such as RWH reduces the cost of water supply compared to conventional large-scale infrastructure such as dams. The Municipality of Chios has estimated that if the 25% of residents install a RWHs, the overall benefit is equivalent to the construction of a dam with effective capacity of 370,000 m 3 which costs about EUR 1,500,000[81].…”
mentioning
confidence: 99%
“…As a basic input factor for social reproduction, water resources participate in regional social reproduction activities, forming a dual water cycle model of ‘nature–society’ in which the social water cycle of regional social reproduction interacts with the natural water cycle. At the same time, the water resources also transform and migrate between regions in the form of ‘virtual water’ or ‘embedded water’ with the trade of goods and services driven economic forces (Fan et al, 2019; Hassan et al, 2016; Xu et al, 2021), and the resulting trade water cycle, together with the natural and social water cycles, constitutes a ternary ‘nature–society–trade’ water cycle model (Figure 1) (Deng et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Since British scholar Allan (1993) first proposed the concept of virtual water in the 1990s, virtual water trade has gradually become a hot research area in water resources management in recent decades. Currently, scholars' research on virtual water involves different dimensions, including revealing the implied virtual water flow pattern of trade in a certain product or industry, studying the virtual water trade pattern at different regional spatial scales, and analysing blue, green and grey water footprints (Fan et al, 2019; Hassan et al, 2016; Xu et al, 2021). Driven by artificial and economic forces, water resources are also involved in the production of goods and services in the form of ‘virtual water’, and the regional water cycle has thus shown the characteristics of the ‘nature–society’ binary water cycle (Fang et al, 2014; Li et al, 2018; Qin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Miglietta et al (2021) showed that the mean amount of virtual water related to fair trade imports in Italy was 7.27 million m 3 for bananas, 22 275 m 3 for cocoa, and 14 334 m 3 for coffee. According to Xu et al (2021), interprovincial virtual water trade in China has decreased water exploitation by 446 billion m 3 in noncommercial conditions of virtual water and 22 provinces in China could save on freshwater consumption at a national scale (Miglietta et al, 2021). Zhai et al (2021) showed that importing cereals from abroad to China had saved national water consumption in China and had reduced environmental impact (Zhai et al, 2021).…”
Section: Introductionmentioning
confidence: 99%